Distinct Synchronous Network Activity During the Second Postnatal Week of Medial Entorhinal Cortex Development - Dawitz, Julia; Kroon, Tim; Hjorth, J. J. Johannes; Mansvelder, Huib D.; Meredith, Rhiannon M. (Frontiers in Cellular Neuroscience, 2020)
The medial entorhinal cortex (MEC) contains specialized cell types whose firing is tuned to aspects of an animal’s position and orientation in the environment, reflecting a neuronal representation of space. The spatially tuned firing properties of these cells quickly emerge during the third postnatal week of development in rodents. Spontaneous synchronized network activity (SSNA) has been shown to play a crucial role in the development of neuronal circuits prior to week 3. SSNA in MEC is well described during the first postnatal week, but there is little data about its development immediately prior to eye opening and spatial exploration. Furthermore, existing data lack single-cell resolution and is not integrated across layers. In this study, we addressed the question of whether the characteristics and underlying mechanisms of SSNA during the second postnatal week resemble that of the first week or whether distinct features emerge during this period. We confirm that in MEC during the second postnatal week, SSNA persists and in fact peaks, and is dependent on ionotropic glutamatergic signaling. However, SSNA differs from that observed during the first postnatal week in two ways: Firstly, EC does not drive network activity in the hippocampus but only in neighboring neocortex. Secondly, GABA does not drive network activity but influences it in a manner that is dependent both on age and receptor type. Therefore, we conclude that while there is a partial mechanistic overlap in SSNA between the first and second postnatal weeks, unique mechanistic features do emerge during the second week, suggestive of different or additional functions of MEC within the hippocampal-entorhinal circuitry with increasing maturation.